A Case of Spontaneous Common Iliac Atery Dissection - Juho Noh; Il Rhee; Minsung Kim; Jonghyun Lee; Kisu Kim; Byungwhan Park (Kosin Medical Journal, 2018)
Spontaneous and isolated dissection of the limb arteries without involvement of the aorta is extremely rare, and has been reported previously in pregnant patients in association with collagen vascular disease, and in cases of high-energy trauma or intensive activity in athletes. There is no consensus yet on indications for medical or surgical therapeutic modality. Due to the rarity of spontaneous dissection of external iliac artery, its natural history has been poorly described. A healthy 50-year-old male with normotension was admitted with an acute onset of left flank pain. Left external iliac artery dissection was diagnosed by abdominal computed tomography.